Carbon / carbon-silicon carbide gradient composite material sagger and preparation method and application thereof
Through the preparation of the silo of the carbon/carbon-silicon carbide gradient composite material, the gradient structure is formed by using chemical vapor phase co-deposition and coating processes, which solves the problems of low strength and easy oxidation of the lithium battery silo, significantly extends the service life and Suitable for mass production.
Patent Information
- Application Number
- CN202411312086.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium battery sash has low strength, easy oxidation and short service life. Especially during the roasting of the positive electrode material of the lithium battery, it is easy to be eroded by lithium ions, resulting in structural damage and shortened service life.
Carbon/carbon-silicon carbide gradient composite material silo, through chemical vapor phase co-deposition density enhancement technology and high-temperature treatment, combined with chemical vapor phase co-deposition coating technology, the proportional gradient distribution of pyrolyzed carbon and silicon carbide from the core to the surface is formed. , improve the strength and corrosion resistance of the silhouette.
It significantly improves the service life of the lithium battery sash and extends it by more than 50%. It is suitable for mass production in the lithium battery field, solving the strength and cost problems.
Smart Images

Figure CN119143514A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery electrode preparation, and in particular to a carbon / carbon-silicon carbide gradient composite material sagger and a preparation method and application thereof. Background Art
[0002] With the rapid development of the lithium battery industry, the demand for lithium battery negative and positive electrode materials has grown rapidly, which has increased the demand for saggers for heat treatment of negative and positive battery materials, and the cost-effectiveness requirements have been improved. Graphite has been widely used as a negative electrode powder and a sagger for heat treatment of lithium iron phosphate positive electrode materials, but graphite has low strength, is fragile, and has poor corrosion resistance. The positive electrode materials of lithium batteries used for roasting are mostly powdered and have strong permeability. The lithium ions in the materials are strong alkaline substances, which are highly corrosive to the sagger materials. During the roasting process of lithium battery positive electrode materials, due to the contact between lithium ions and saggers, lithium ions can precipitate Si, Al, Mg and other ions in mullite, thereby destroying the microstructure of the sagger, and the sagger is corroded, resulting in a significant shortening of the service life of the sagger.
[0003] Carbon / carbon composite material is a carbon fiber reinforced carbon matrix composite material. It has excellent properties such as low density, high specific strength and specific modulus, high temperature and corrosion resistance, small thermal expansion coefficient, good dimensional stability, and strong designability, and is widely used in military and civilian fields.
[0004] Therefore, it is urgent to design a sagger for heat treatment of lithium battery negative electrode powder and lithium iron phosphate material based on carbon / carbon composite materials to fundamentally solve its strength and cost problems and to increase the service life of the sagger for heat treatment of lithium battery negative electrode powder and lithium iron phosphate material. Summary of the invention
[0005] In view of the defects of existing graphite saggers, such as low strength, easy oxidation and short service life, the present invention provides a carbon / carbon-silicon carbide gradient composite material sagger and its preparation method and application. The sagger is densified by chemical vapor co-deposition densification technology, then subjected to high temperature treatment, mechanical processing, and finally subjected to surface coating by chemical vapor co-deposition coating process to prepare a carbon / carbon-silicon carbide gradient composite material sagger. The ratio of pyrolytic carbon and silicon carbide that wraps the growth of carbon fibers is distributed in a gradient, and the ratio of pyrolytic carbon and silicon carbide from the core of the sagger to the inner and outer surfaces is distributed in a gradient, which has high strength. At the same time, the surface carbon content and the reaction rate of the sagger surface with oxygen at high temperature are reduced, which fundamentally solves the strength and easy oxidation problems of the current saggers for lithium batteries and effectively improves the service life of the sagger. The technical scheme of the present invention is as follows:
[0006] A method for preparing a carbon / carbon-silicon carbide gradient composite material sagger, comprising: subjecting a silicon-containing carbon fiber composite sagger preform to a chemical vapor co-deposition densification process and a chemical vapor co-deposition coating process to obtain a carbon / carbon-silicon carbide gradient composite material sagger;
[0007] The method for preparing the silicon-carbon fiber composite preform comprises:
[0008] The surface density is 280~600g / m 2 Carbon fiber plain cloth or carbon fiber twill cloth with surface density of 80-120g / m 2 The short fiber web is needle-punched into a whole to form a carbon fiber sagger preform;
[0009] The weight ratio of the carbon fiber plain cloth or carbon fiber twill cloth to the short fiber web is controlled at 9:1-7:3, and the density is 0.45-0.8 g / cm 3 , thickness is 15~25mm;
[0010] The carbon fiber sagger preform is put on the mold so that the inner surface of the carbon fiber sagger preform is well fitted with the outer surface of the mold, and then sprayed or impregnated with a silicon-containing precursor resin and / or a silicon-containing organic binder, left for 1 to 3 hours, and placed in a vacuum oven for curing and shaping. The temperature is controlled at 150 to 300° C., kept warm for 1 to 5 hours, cooled, and demolded to obtain a shaped silicon-containing carbon fiber composite preform.
[0011] Preferably, the mold is any one of a steel mold or a graphite mold.
[0012] Preferably, the resin of the silicon-containing precursor is a mixture of phenolic resin or furan resin and polymethylsilane.
[0013] Preferably, the volume ratio of the carbon source gas to the trichloromethylsilane gas in the chemical vapor co-deposition densification process is 9:1 to 2:8.
[0014] Preferably, the carbon source gas is natural gas, propane, propylene, or a mixture of any two thereof.
[0015] Preferably, the chemical vapor co-deposition densification process is specifically as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas + hydrogen, which are introduced into the deposition chamber in proportion at the same time, the deposition temperature is 1000-1120°C, the furnace pressure is 1.5-10 kPa, the densification time is 150-300 hours, and the silicon-containing carbon fiber composite preform is densified to 1.4-1.6 g / cm 3 After that, high temperature treatment is carried out at a temperature of 1300-2000°C for 2-10 hours, and then machining is performed to product size to obtain a carbon / carbon-silicon carbide gradient composite material sagger.
[0016] Preferably, the co-deposition chemical vapor deposition coating process is specifically as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas and hydrogen, which are introduced into the deposition chamber at the same time in proportion, and the volume ratio of the carbon source gas to the trichloromethylsilane gas is 1:9 to 5:5. The volume ratio of the gas is 1050 to 1150°C, the furnace pressure is 1.5 to 10 kPa, and the coating time is 10 to 50 hours to obtain a carbon / carbon-silicon carbide gradient composite material with a density of 1.5 to 1.8 g / cm 3 .
[0017] A carbon / carbon-silicon carbide gradient composite material sagger prepared by the above preparation method.
[0018] An application of the above-mentioned carbon / carbon-silicon carbide gradient composite material sagger in the preparation of lithium battery electrode materials.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The present invention designs and prepares a carbon / carbon-silicon carbide gradient composite material sagger. When the preform is cured and shaped, polymethylsilane, a precursor of silicon carbide, is added to a resin or an organic binder to obtain a carbon fiber composite preform containing a silicon carbide precursor. When carbonized by heating, the obtained preform contains silicon carbide. Then, chemical vapor co-deposition is used for densification, and pyrolytic carbon and silicon carbide matrix are deposited simultaneously, so that the pyrolytic carbon and silicon carbide matrix that wrap the growth of carbon fiber are deposited simultaneously. During the deposition process, the ratio of the two is adjusted to obtain a gradient structure, and the fiber surface is exposed to the pyrolytic carbon and silicon carbide. The ratio of carbon to silicon carbide on the surface of the substrate is distributed in a gradient from low to high; finally, when the chemical vapor co-deposition process is used for coating, the ratio of silicon carbide is increased, and a gradient structure of pyrolytic carbon and silicon carbide from the core to the surface can be further formed in the sagger. The obtained carbon / carbon-silicon carbide gradient composite material sagger has high strength and good corrosion resistance, and can effectively reduce or avoid the reaction between the inner and outer surface layers of the sagger and oxygen. Compared with the graphite sagger (generally with a service life of 4 to 5 months), the service life of the sagger is increased by more than 50%, which is suitable for the mass production of saggers in the field of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the deposition of pyrolytic carbon (including silicon carbide) around carbon fibers in the present invention. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is described below through specific embodiments.
[0023] Unless otherwise specified, the raw materials, equipment, etc. involved in the present invention are common commercially available products.
[0024] Example 1
[0025] A method for preparing a carbon / carbon-silicon carbide gradient composite material sagger is prepared by subjecting a silicon-containing carbon fiber composite preform to a chemical vapor co-deposition densification process and a co-deposition chemical vapor deposition process; the method for preparing the silicon-containing carbon fiber composite preform comprises:
[0026] The surface density is 280~600g / m 2 Carbon fiber plain cloth or carbon fiber twill cloth with surface density of 80-120g / m 2 The short fiber web is needle-punched into a whole to form a carbon fiber preform;
[0027] The weight ratio of the carbon fiber plain cloth or carbon fiber twill cloth to the short fiber web is controlled at 9:1-7:3, and the density is 0.45-0.8 g / cm 3 , thickness is 15~25mm;
[0028] The carbon fiber preform is put on the mold so that the inner surface of the sagger preform fits well with the outer surface of the mold, and then sprayed or impregnated with a resin containing a silicon precursor and / or a silicon-containing organic binder, left for 1 to 3 hours, and placed in a vacuum oven for curing and shaping. The temperature is controlled at 150 to 300° C., kept warm for 1 to 5 hours, cooled, and demolded to obtain a shaped silicon-containing carbon fiber composite preform.
[0029] Wherein, the mold is any one of a steel mold or a graphite mold.
[0030] Wherein, the resin of the silicon-containing precursor is a mixture of phenolic resin or furan resin and polymethylsilane.
[0031] Among them, the volume ratio of carbon source gas to trichloromethylsilane gas in the chemical vapor co-deposition densification process is 8:2 and gradually adjusted to 6:4 gas volume ratio. (The change rate or law needs to be stated)
[0032] Wherein, the carbon source gas is natural gas, propane, propylene, or a mixture of any two thereof.
[0033] The chemical vapor co-deposition densification process is as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas + hydrogen, which are introduced into the deposition chamber in proportion at the same time, the deposition temperature is 1000-1120°C, the furnace pressure is 1.5-10 kPa, the densification time is 200 hours, and the silicon-carbon fiber composite preform is densified to 1.5-1.6 g / cm 3 After that, it is subjected to high temperature treatment at 1800°C for 3 hours, and then machined to product size to obtain a carbon / carbon-silicon carbide gradient composite material sagger.
[0034] The co-deposition chemical vapor deposition coating process is specifically as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas + hydrogen, which are introduced into the deposition chamber at the same time in proportion, and the volume ratio of the carbon source gas to the trichloromethylsilane gas is 2:8 to 3:7. The volume ratio of the gas is 1080±5°C, the furnace pressure is 3kPa, and the coating time is 30 hours. A carbon / carbon-silicon carbide gradient composite material sagger is obtained with a density of 1.60 to 1.75 g / cm 3 .
[0035] The service life of the obtained carbon / carbon-silicon carbide gradient composite material sagger is 12 months.
[0036] Comparative Example 1
[0037] The pyrolytic carbon + silicon carbide matrix is not obtained by chemical vapor co-deposition densification process, and the carbon / carbon composite sagger is prepared by chemical vapor deposition densification process. The pyrolytic carbon + silicon carbide is coated by chemical vapor co-deposition to obtain a carbon / carbon-silicon carbide partial gradient composite sagger with a density of 1.60-1.65g / cm 3 , other processes are the same as in Example 1.
[0038] The service life of the obtained carbon / carbon-silicon carbide partially gradient composite material sagger is 8.5 months.
[0039] Comparative Example 2
[0040] The pyrolytic carbon + silicon carbide matrix is obtained without using the chemical vapor co-deposition densification process, and the surface coating is formed without using the chemical vapor co-deposition coating process to obtain a carbon / carbon composite material sagger with a density of 1.50-1.55 g / cm 3 , the rest is the same as in Example 1.
[0041] The service life of the obtained carbon / carbon composite material sagger is 7 months.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the principle and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon / carbon-silicon carbide gradient composite material sagger, characterized in that: include: The silicon-carbon fiber composite sagger preform is subjected to chemical vapor co-deposition densification process and chemical vapor co-deposition coating process to obtain a carbon / carbon-silicon carbide gradient composite material sagger; The method for preparing the silicon-carbon fiber composite preform comprises: The surface density is 280~600g / m 2 Carbon fiber plain cloth or carbon fiber twill cloth with surface density of 80-120g / m 2 The short fiber web is needle-punched into a whole to form a carbon fiber sagger preform; The weight ratio of the carbon fiber plain cloth or carbon fiber twill cloth to the short fiber web is controlled at 9:1-7:3, and the density is 0.45-0.8 g / cm 3 , thickness is 15~25mm; The carbon fiber sagger preform is put on the mold so that the inner surface of the carbon fiber sagger preform is well fitted with the outer surface of the mold, and then sprayed or impregnated with a silicon-containing precursor resin and / or a silicon-containing organic binder, left for 1 to 3 hours, and placed in a vacuum oven for curing and shaping. The temperature is controlled at 150 to 300° C., kept warm for 1 to 5 hours, cooled, and demolded to obtain a shaped silicon-containing carbon fiber composite preform.
2. The preparation method according to claim 1, characterized in that: The mold is any one of a steel mold or a graphite mold.
3. The preparation method according to claim 1, characterized in that: The resin of the silicon-containing precursor is a mixture of phenolic resin or furan resin and polymethylsilane.
4. The preparation method according to claim 1, characterized in that: The volume ratio of the carbon source gas to the trichloromethylsilane gas in the chemical vapor co-deposition densification process is 9:1 to 2:
8.
5. The preparation method according to claim 4, characterized in that: The carbon source gas is natural gas, propane, propylene, or a mixture of any two thereof.
6. The preparation method according to claim 5, characterized in that: The chemical vapor co-deposition densification process is specifically as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas + hydrogen, which are introduced into the deposition chamber in proportion at the same time, the deposition temperature is 1000-1120°C, the furnace pressure is 1.5-10kPa, the densification time is 150-300 hours, and the silicon-containing carbon fiber composite preform is densified to 1.4-1.6g / cm 3 After that, high temperature treatment is carried out at a temperature of 1300-2000°C for 2-10 hours, and then machining is performed to product size to obtain a carbon / carbon-silicon carbide gradient composite material sagger.
7. The preparation method according to claim 1, characterized in that: The co-deposition chemical vapor deposition coating process is specifically as follows: one gas is trichloromethylsilane as a silicon carbide precursor, hydrogen is a diluent gas, nitrogen or argon is a carrier gas, and the other gas is a carbon source gas and hydrogen, which are introduced into the deposition chamber at the same time in proportion, and the volume ratio of the carbon source gas to the trichloromethylsilane gas is 1:9-5:
5. The volume ratio of the gas is 1050-1150°C, the furnace pressure is 1.5-10 kPa, and the coating time is 10-50 hours to obtain a carbon / carbon-silicon carbide gradient composite material with a density of 1.5-1.8 g / cm 3 .
8. A carbon / carbon-silicon carbide gradient composite material sagger prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the carbon / carbon-silicon carbide gradient composite material sagger as claimed in claim 8 in the preparation of lithium battery electrode materials.
Citation Information
Patent Citations
Carbon / carbon-silicon carbide gradient composite material for photovoltaic thermal field as well as preparation method and application of carbon / carbon-silicon carbide gradient composite material
CN118146021A
Cited By
Continuous carbon fiber reinforced silicon carbide sagger and preparation method thereof
CN119306497A
